Classical rhetoric & its Christian & secular tradition from ancient to modern times - Kennedy, George A. (George Alexander), 1928-2022 (University of North Carolina Press, 1999)
Since its original publication by UNC Press in 1980, this book has provided thousands of students with a concise introduction and guide to the history of the classical tradition in rhetoric, the ancient but ever vital art of persuasion. Now, George Kennedy offers a thoroughly revised and updated edition of Classical Rhetoric and Its Christian and Secular Tradition. From its development in ancient Greece and Rome, through its continuation and adaptation in Europe and America through the Middle Ages and Renaissance, to its enduring significance in the twentieth century, he traces the.